2021
DOI: 10.1016/j.biopha.2021.112228
|View full text |Cite
|
Sign up to set email alerts
|

A digital health platform for assisting the diagnosis and monitoring of COVID-19 progression: An adjuvant approach for augmenting the antiviral response and mitigating the immune-mediated target organ damage

Abstract: Coronavirus disease 2019 (COVID-19), which is a respiratory illness associated with high mortality, has been classified as a pandemic. The major obstacles for the clinicians to contain the disease are limited information availability, difficulty in disease diagnosis, predicting disease prognosis, and lack of disease monitoring tools. Additionally, the lack of valid therapies has further contributed to the difficulties in containing the pandemic. Recent studies have reported that the dysregulation of the immune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 194 publications
(227 reference statements)
0
21
0
Order By: Relevance
“…Looking into the “3rd and the 4th dimensions” does not finish the quest to comprehend biological systems [ 15 ]. Our findings suggest that in addition to time, adding an individualized variability, viewed as “the fifth dimension,” is required for improved analysis of isolated systems [ 31 , 32 , 33 , 34 ]. Considering an individualized response, which involves both the time and the magnitude of the response, rather than looking into means of the group, maybe needed for better design of precision medicine [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Looking into the “3rd and the 4th dimensions” does not finish the quest to comprehend biological systems [ 15 ]. Our findings suggest that in addition to time, adding an individualized variability, viewed as “the fifth dimension,” is required for improved analysis of isolated systems [ 31 , 32 , 33 , 34 ]. Considering an individualized response, which involves both the time and the magnitude of the response, rather than looking into means of the group, maybe needed for better design of precision medicine [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials are ongoing to determine the use of irregularity for overcoming drug resistance in patients who have lost their response to drugs [ 25 , 43 , 68 , 76 , 85 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 153 , 154 ]. Patients are treated according to a regimen that introduces irregularity in the dose and intervals of drug administration, maintaining them within the drug’s therapeutic window and a physician’s pre-determined range [ 141 ].…”
Section: A Three-phase Roadmap For Developing a Platform For Overcomi...mentioning
confidence: 99%
“…It is essential to establish and quantify cellular and whole organ patterns of variability and then implement them into the algorithm for improving accuracy [ 25 , 43 , 68 , 76 , 85 , 97 , 100 , 101 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 153 , 154 , 155 , 156 , 157 , 158 ]. Important information is also obtained by evaluating single-cell variabilities in gene expression, proteomics, metabolomics, and epitope expression performed on cells harvested from patients before and after therapy for chronic disease.…”
Section: A Three-phase Roadmap For Developing a Platform For Overcomi...mentioning
confidence: 99%
“…Drug resistance is a significant health issue during chronic opioid use for pain [108]. Studies showed a similar resistance for many other drugs like anti-depressants, anti-diabetics, and diuretics [64,65,75,80,[102][103][104][109][110][111][112][113][114][115][116][117][118][119][120][121][122][123][124][125][126].…”
Section: Overcoming Plateaus In Muscle Training By Introducing Subjec...mentioning
confidence: 99%
“…Second-generation artificial intelligence systems can implement variability into training and therapeutic regimens for overcoming biological tolerance and plateaus for various chronic diseases [80,[102][103][104][112][113][114][115][116][117][118][119][120][121][122][123][124][125][126]. Introducing variability to improve muscle performance can be implemented in two stages.…”
Section: Overcoming Plateaus In Muscle Training By Introducing Subjec...mentioning
confidence: 99%